مدارات فعل التخييل في التجربة القصصية ل محمد الصديق معوش اعتراف/ذهب مع المطر - بوعافية, بالحسروف, خديجة ابتسام; محبوب, ربى (University of El-oued, 2022)
من خلال هذه الدراسة الموسومة ب "مدارات فعل التخييل في التجربة القصصية لمحمد الصديق معوش (ذهب مع المطر/ اعتراف)" سعينا للكشف عن أهم السياقات التي جاءت على شاكلتها أفعال التخييل، وإبراز مدى تحكم الذات الساردة في تطور الأحداث، وكذلك غياب صورة الكاتب حضوريا، وذهبنا أيضا إلى إبراز التناص الأدبي في القصص من خلال الأعمال التي تقاطع معها الكاتب. ورد البحث في مقدمة ومدخل تمهيدي، فصليين تطبيقيين وخاتمة وأخيرا الملحق؛ تناولنا في المدخل التمهيدي ماهية القصة وأنواعها وأهم عناصرها، أما الفصل الأول فكان للخبر باعتباره نوعا من السيرة الذاتية من خلال قصتي (اعتراف/ سرقة بديرو الشهيرة)، أما الفصل الثاني فكان للحدث من جهة التناص الأدبي من خلال قصتي (ذهب مع المطر/ رحلة في الظلام)، أما الخاتمة فكانت للنتائج المتوصل إليها من خلال الدراسة، وفي الأخير ملحق حول السيرة الذاتية والأدبية للكاتب "محمد الصديق معوش". Through this study that is named (the contexts of the imaginary act in the story experiment,"we chose as an example the story" went with the rain "for is writer mohammed al-seddikmaouch, to reveal the most important context that came with the imaginary acts, and we tried to show how controlling is the narrator over the development of events, as well as the absence and presence of the writer’s image. We also attempted to highlight the literary decreasing in the stories througt the works that the writer interrupted. So that, we presented our study in a from of an introduction, an introductory entry, two pratical chapters, and finally an index. In the introductory entry, we defined what is a story, what are its types and its elements. While in the first chapter, we spoke about the event as it is considered a type of a biography through the two stories: "conffession, and the famous badirou robbery". In the second chapter, we dealt with the event on the literary decreaing side through the two stories:" went with the rain, and a journey in the dark". We concluded with the results reached by our study, and finellyattachedit with an sepplement that includs the biography of the writer ;"mohammed al-seddikmaouch"
Keywords: التخييل . التجربة. القصصية